Dakwah dalam Al-Qur’an: Sebuah Pijakan Pengembangan Metode Dakwah Kontemporer - Iftitah Jafar; Mudzhira Nur Amrullah (Studia Quranika, 2021)
The aims of this paper is revealing the methods of da’wa in Qur’anic perspective. Qur’an provides variey of grand methods of da’wa that should be explored. These methods have been practiced by the messengers of Allah in their tme. Nowadays many new methods of da’wa have been emerged in the middle of society. However we do not have lot of informations on the correlation of these methods with those on the Qur’an. This study is a qualitative descriptive method based on thematic approach. Verses of method of da’waare collected, classified, and analyzed in Qur’anic perspective. The result of study showed some grand methods of da’wa conveyed in the Qur’an includes: philosophy method, guidance method, debate method, provement approach, challenging approach, and cultural approach. These methodes of da’wa contribute in the formulation of new approaches of da’wa.